QARAQALPAQ HÁM INGLIS TILLERINDEGI ATLÍQTÍŃ KÓPLIK SAN KÓRSETKISHLERINIŃ SEMANTIKALÍQ ÓZGESHELIKLERI - Bekbergenov, H.U. (SCIENCE and SOCIETY, 2024)
This article deals with the semantic peculiarities of plural forms of nouns in the English and Karakalpak languages. Different meanings of proper, material and abstract nouns in plural forms have been analysed based on the related materials on this subject.